Participatory Evaluation of Climate-Smart Risk Maps and Adaptation Plans (CS-MAP) at Community Level for the Coastal Agriculture of Bangladesh - Ali, A M M Mostafa; Rahman, Md. Mostafizur; Saha, Champa Rani; Rahman, Syed Arman Akib; Haque, Md. Ehsanul; Ryhan, Md Abu; Yen, Bui Tan; Nelson, Katherine; Vu, Trang; Vu, Quyet; Tran, Nguyen Bao; Salahuddin, Ahmad (CGIAR Initiative on Asian Mega-Deltas, 2024)
Bangladesh, an agricultural country, is highly vulnerable to climate change and is ranked seventh among the most extreme disaster-prone countries in the world (UNDP, 2023). The country faces exceptional challenges due to their low-lying and flat topography, subjected to riverine flooding (due to sea level rise), frequent cyclones, storm surges, heavy rainfall, tornados, river bank erosion, salinity, high population density, high level of poverty, and solely reliance of livelihoods on climate-sensitive sectors and extreme weather events resulting from climate change (Islam et al., 2024).